Assessing Digital Transformation Readiness: Digital Leadership and Human Resource Capacity as Influencing Factors at SMP 72 Maluku Tengah - Desembra Sohilait; Andi Kristanto; Syunu Trihantoyo (Islamic Education Management Study Program, Faculty of Tarbiyah, Sunan Drajat Islamic Boarding School Institute, Lamongan, East Java, Indonesia., 2026)
Digital transformation in educational institutions often falls into structural readiness without guaranteeing operational execution. This study aims to assess digital transformation readiness and test the influence of digital leadership and human resource capacity on implementation readiness. The method used is descriptive-correlational quantitative with a survey design. Data collection was conducted using a Likert-scale questionnaire consisting of 30 items. The research sample involved a census population of 21 teachers and educational staff at Junior High School 72 Central Maluku. The research hypotheses proposed that digital leadership and human resource capacity positively affect implementation readiness. Findings show that overall readiness is in the very high category. However, a statistical paradox exists where digital leadership has no significant effect, while human resource capacity becomes a highly significant dominant predictor. The findings indicate that linear assumptions in previous leadership-centric literature may need to be reconsidered, and show the possibility of a novel human-agency-centric perspective, positioning human resource capacity as the actual mechanism for technology institutionalization. Consequently, it is suggested that educational digital transformation policies should shift focus from mere managerial support to the institutionalization of operational competencies, making human resource interventions the primary priority for the sustainability of the school's digital ecosystem